Back elevation of the mulaprasada of the Chaunsath Yogini Temple - Temples of India Project Team (Jio Institute, 2024)
A view of the profusely carved east-facing elevation of the Chaunsath Yogini temple. The mouldings of the mulaprasada are carved with figural sculptures and geometric patterns, one of the facets that distinguish the temple from other structures within the Arthuna temple complex. The principal niche is empty. Only two tiers of the shikhara of the temple have survived, along with the shukanasa (an embellished panel) which forms the base of the cardinal band in the shikhara.